Ephemeral narrative structures. Resonances and echoes of the Sonsbeek pavilion by Aldo van Eyck in the Hanover pavilion by Peter Zumthor - Sonntag, Franca Alexandra; Montoro Coso, Ricardo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
In 1995; several years before the inauguration of the Universal Exposition in the year 2000 in Hannover with the theme "Mankind, nature and technology; creating a New World "; The Swiss authorities decide to convene a competition idea to select the best project to represent the country at this event. Among more than one hundred projects presented for an ephemeral pavilion, the winner of the second and final phase was the proposal presented by Peter Zumthor under the motto Batterie. Away from the container concept with content; replicated many times in this type of exhibition, the proposal will emerge from experience of going through its spaces between a series of stacking of wooden slats. A temporary "pentagram" where different notes and tones sprout from the sequence. This architectural melody has some recognizable chords in another pavilion, the original by Aldo van Eyck inaugurated in 1965 in Sonsbeek. Spaces between walls; resonances and echoes between both fleeting exhibition proposals.
Keywords: Peter Zumthor; Aldo van Eyck; pavilion; wall; composition; phenomenology